(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2015)
In the present study, an attempt has been taken to evaluate the effect of sodium lauryl sulphate (SLS) and glyceryl mono stearate (GMS) as solubility enhancers on the release profile of a poorly soluble drug, carbamazepine. Matrix tablets of carbamazepine were prepared by wet granulation technique using hydrophilic polymers (10% of Methocel K15 MCR and 10% of Methocel K100LV CR) as release controlling agents. Varying amounts of SLS and GMS were used in six different formulations to observe the impact on the release rate and mechanism of drug release. The dissolution study of carbamazepine from these extended release matrix tablets was conducted for 24 hours using basket method in 900 ml distilled water as dissolution medium. The data obtained from the dissolution studies were explored and explained with the help of zero order, Higuchi, first order, Korsmeyer- Peppas and Hixson-Crowell equations. It was found that the dissolution rate of carbamazepine with the formulation containing SLS was higher than GMS containing formulation and increased concentration of SLS increasing the release rate. Where there was no SLS or smaller amount of SLS or GMS release rate was decreased. Formulation having equal ratio of SLS and GMS did not show the desire release profile. The drug release mechanism followed mainly super case II transport. These results clearly demonstrated that the dissolution rate, extent and mechanism of carbamazepine release could be changed by optimizing the amount of SLS and GMS in the tablet formulation. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21894 Dhaka Univ. J. Pharm. Sci. 13(2): 167-173, 2014 (December)